Efficacy and safety of antibody–drug conjugates in the treatment of urothelial cell carcinoma: a systematic review and meta-analysis of prospective clinical trials - Ren, Jun-Wei; Chen, Ze-Yu; Bai, Yun-Jin; Han, Ping (Frontiers in Pharmacology, 2024)
Introduction: Urothelial carcinoma (UC) is a refractory disease for which achieving satisfactory outcomes remains challenging with current surgical interventions. Antibody–drug conjugates (ADCs) are a novel class of targeted therapeutics that have demonstrated encouraging results for UC. Although there is a limited number of high-quality randomized control trials (RCTs) examining the use of ADCs in patients with UC, some prospective non-randomized studies of interventions (NRSIs) provide valuable insights and pertinent information. We aim to assess the efficacy and safety of ADCs in patients with UC, particularly those with locally advanced and metastatic diseases. Methods: A systematic search was conducted across PubMed, Embase, the Cochrane Library, and Web of Science databases to identify pertinent studies. Outcomes, such as the overall response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), adverse events (AEs), and treatment-related adverse events (TRAEs), were extracted for further analyses. Results: Twelve studies involving 1,311 patients were included in this meta-analysis. In terms of tumor responses, the pooled ORR and DCR were 40% and 74%, respectively. Regarding survival analysis, the pooled median PFS and OS were 5.66 months and 12.63 months, respectively. The pooled 6-month PFS and OS were 47% and 80%, while the pooled 1-year PFS and OS were 22% and 55%, respectively. The most common TRAEs of the ADCs were alopecia (all grades: 45%, grades ≥ III: 0%), decreased appetite (all grades: 34%, grades ≥ III: 3%), dysgeusia (all grades: 40%, grades ≥ III: 0%), fatigue (all grades: 39%, grades ≥ III: 5%), nausea (all grades: 45%, grades ≥ III: 2%), peripheral sensory neuropathy (all grades: 37%, grades ≥ III: 2%), and pruritus (all grades: 32%, grades ≥ III: 1%). Conclusion: The meta-analysis in this study demonstrates that ADCs have promising efficacies and safety for patients with advanced or metastatic UC. Systematic review registration:https://www.crd.york.ac.uk/prospero/, identifier: CRD42023460232